2003
DOI: 10.1016/s0278-2626(03)00042-3
|View full text |Cite
|
Sign up to set email alerts
|

Face processing in adolescents with autistic disorder: The inversion and composite effects

Abstract: Two experiments with upright and inverted face and object images were carried out to investigate whether face processing in autism is more feature-based than in individuals with typical development. Participants were 17 high-ability adolescents with autistic disorder (16-24 years), 24 typically developing children (9-10 years) and 16 adults (18-33 years). In Experiment 1, a normal inversion effect was found for the adolescents with autism in a standard face recognition paradigm with reduced memory demands, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
162
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 43 publications
13
162
0
1
Order By: Relevance
“…The one line of investigation has shown that autistic individuals perform poorly on tasks requiring face processing, including identity recognition as well as discrimination of gender, gaze direction and emotion (Teunisse & De Gelder, 2003). The second line of investigation has been concerned with the extent to which autistic individuals are able to derive a coherent or meaningful whole from the local elements present in visual input.…”
Section: Discussionmentioning
confidence: 99%
“…The one line of investigation has shown that autistic individuals perform poorly on tasks requiring face processing, including identity recognition as well as discrimination of gender, gaze direction and emotion (Teunisse & De Gelder, 2003). The second line of investigation has been concerned with the extent to which autistic individuals are able to derive a coherent or meaningful whole from the local elements present in visual input.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with ASD are generally slower on tasks of face processing compared with typically developing controls [Teunisse and de Gelder, 2003;Wallace et al, 2006], making between group comparisons of reaction time (RT) data difficult to interpret. Within-group comparisons remain informative, however.…”
Section: A Test Of Holistic Processingmentioning
confidence: 99%
“…The few studies that have included nonface objects as control stimuli have found that affected individuals were unimpaired [Hauck et al, 1998;Teunisse and de Gelder, 2003] or showed superior object-processing performance [Blair et al, 2002;Boucher and Lewis, 1992]. The combination of impaired face and intact object processing has led to the proposal that individuals with ASD fail to use secondorder configural [Barton et al, 2004;Davies et al, 1994;Teunisse and de Gelder, 2003] or holistic [Deruelle et al, 2004;Joseph and Tanaka, 2003;Lopez et al, 2004;Serra et al, 2003;Teunisse and Degelder, 1994] information for face discrimination, but instead rely on feature processing [Davies et al, 1994;Deruelle et al, 2004;Lahaie et al, 2006;Langdell, 1978]. Additionally, the paired observations of impaired configural processing and intact or superior feature processing have been interpreted by some researchers [Davies et al, 1994;Deruelle et al, 2004] as supporting the weak central coherence theory of ASD, which claims that individuals with ASD have a general cognitive style of focussing on the parts of visual stimuli rather than the contextual whole [Happe and Frith, 2006;Frith, 1983, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural phenomena, such as the face inversion effect (FIE), the composite face effect (CFE), and the global precedence effect (GPE), have been identified as the "signatures" or strong markers for holistic visual processing. These are well-established, robust, and related tasks capable of identifying deficits in holistic processing in other neuropsychiatric disorders such as prosopagnosia, autism and schizophrenia (Teunisse and de Gelder, 2003;Behrmann et al, 2005;Le Grand et al, 2006;Duchaine et al, 2007;Bookheimer et al, 2008;Butler et al, 2008). The present study aimed to use these paradigms to examine whether the over focus on details in appearance in BDD is attributable to a specific impairment in global processing.…”
Section: Introductionmentioning
confidence: 99%